The Prevalence of Depression among Undergraduates of a Selected Medical Faculty in Sri Lanka - Kodagoda, A.S.K; Meegoda, M.K.D.L (Faculty of Allied Health Sciences, University of Sri Jayewardenepura, 2020)
Introduction: Depression is a common mental disorder which can lead to major problems such as suicidal attempts. It is well known that the demands and pressure on undergraduates in medical faculties create tremendous challenges which result in an extensive range of psychological ailments like depression. The objective of this study was to determine the prevalence of different levels of depression among undergraduates in a selected medical sciences faculty in Sri Lanka. Methods: A descriptive cross-sectional study was conducted using a convenient sampling technique among students in a selected medical faculty. The Depression Anxiety Stress Scale-21 (DASS-21) was used to assess depressive symptoms of the respondents. Descriptive analysis was done using SPSS version 23. Results: Mean age of the sample (n=397) was 24.1±2.5 years. The mean score obtained for depression was 10.5±8.3. Only 38.5% of the respondents had normal level of depressive symptoms while 7.1% and 4.0% of the respondents presented severe and extremely severe symptoms, respectively. Age (p=0.011) and academic year (p=0.001) showed a significant association with depression. Conclusions: The study demonstrates a considerable prevalence in different levels of depressive symptoms among undergraduates who are enrolled in medical and allied health sciences programmes. Therefore, it would be highly beneficial to reduce depressive symptoms by early identification. Studies to identify causes and interventional studies will contribute to implement measures to improve identification, and reduce the prevalence of depression among undergraduates.
Keywords: Depression, Undergraduates, Mental disorder